2014
DOI: 10.1002/asia.201402250
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 1,4,7,10‐Tetra‐azacyclododecan‐1,4,7,10‐tetra‐azidoethylacetic Acid (DOTAZA) and Related “Clickable” DOTA Derivatives

Abstract: Herein, we report the synthesis of two enantiomeric DOTAZA esters and a related DOT3AZA ester. These compounds are tunable analogues of the well-known chelator DOTA and can be easily functionalized through click chemistry of the side-chain azide groups. Like DOTA, DOTAZA forms complexes with various di- and trivalent metals, as demonstrated in the synthesis and structural analysis of CuDOTAZA and the preparation of GdDOTAZA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 75 publications
0
28
0
Order By: Relevance
“…Consistent with the number of examples given, structures decoratedw ith alkyne functionalities ( Figure 4) [25][26][27][28][29][30] are encountered more frequently than those with azides ( Figure 5). For example, clickable forms of the highly popular DOTA [35] were obtained by amide formation with propargylamine or 3-azidopropylamine, affording compounds 2 [26] or 9, [31] respectively.H owever,s tructures like DOTAZA (10), [32] which are specifically designed for click conjugation and whose synthesis as pure diastereomers requires considerable effort, highlight the growing interest in clickable chelators,w hich,i nt urn, is rooted in the aforementioned availability of ab road selection of clickable functional building blocks. For example, clickable forms of the highly popular DOTA [35] were obtained by amide formation with propargylamine or 3-azidopropylamine, affording compounds 2 [26] or 9, [31] respectively.H owever,s tructures like DOTAZA (10), [32] which are specifically designed for click conjugation and whose synthesis as pure diastereomers requires considerable effort, highlight the growing interest in clickable chelators,w hich,i nt urn, is rooted in the aforementioned availability of ab road selection of clickable functional building blocks.…”
Section: Azide-and Alkyne-decorated Bifunctional Chelatormentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with the number of examples given, structures decoratedw ith alkyne functionalities ( Figure 4) [25][26][27][28][29][30] are encountered more frequently than those with azides ( Figure 5). For example, clickable forms of the highly popular DOTA [35] were obtained by amide formation with propargylamine or 3-azidopropylamine, affording compounds 2 [26] or 9, [31] respectively.H owever,s tructures like DOTAZA (10), [32] which are specifically designed for click conjugation and whose synthesis as pure diastereomers requires considerable effort, highlight the growing interest in clickable chelators,w hich,i nt urn, is rooted in the aforementioned availability of ab road selection of clickable functional building blocks. For example, clickable forms of the highly popular DOTA [35] were obtained by amide formation with propargylamine or 3-azidopropylamine, affording compounds 2 [26] or 9, [31] respectively.H owever,s tructures like DOTAZA (10), [32] which are specifically designed for click conjugation and whose synthesis as pure diastereomers requires considerable effort, highlight the growing interest in clickable chelators,w hich,i nt urn, is rooted in the aforementioned availability of ab road selection of clickable functional building blocks.…”
Section: Azide-and Alkyne-decorated Bifunctional Chelatormentioning
confidence: 99%
“…To some extent, esterification can preventi nteractiono fC u II with the pendanta rm donor sites, although amide oxygens can also functiona sd onors here. Examples for azide-functionalized chelators (9 [31] ; 10 [32] ; 11 [33] ; 12 [34] ). In accordance with this rationale, Knçr et al reported that CuAAC of 1 with azide-decorated Tyr 3 -octreotide,f ollowed by TFAd eprotection,y ieldedt he Cu II complex of the desired conjugate, thus requiring additional treatment with Na 2 S(aq) to remove the metal.…”
Section: Azide-and Alkyne-decorated Bifunctional Chelatormentioning
confidence: 99%
“…[18] Both enantiomerically pure triflates have been prepared from (R)-and (S)-malic acid, respectively. Scheme 2.…”
Section: Resultsmentioning
confidence: 99%
“…We previously reported the preparation and crystallization of the copper complex. [18] Herein, we report the synthesis of the corresponding In 3+ and Y 3+ DOTAZA complexes 7 and 8 with (R,R,R,R)-DOTAZA as a ligand (Scheme 4). After purification by flash chromatography with RP-18 silica, the Y 3+ complex 7 and the In 3+ complex 8 were ob-tained.…”
Section: Y-dotaza and In-dotazamentioning
confidence: 99%
“…Consistent with the number of examples given, structures decoratedw ith alkyne functionalities ( Figure 4) [25][26][27][28][29][30] are encountered more frequently than those with azides ( Figure 5). [31][32][33][34] Mosto ft hem were obtained by straightforward modifications of established, commercially available compounds. For example, clickable forms of the highly popular DOTA [35] were obtained by amide formation with propargylamine or 3-azidopropylamine, affording compounds 2 [26] or 9, [31] respectively.H owever,s tructures like DOTAZA (10), [32] which are specifically designed for click conjugation and whose synthesis as pure diastereomers requires considerable effort, highlight the growing interest in clickable chelators,w hich,i nt urn, is rooted in the aforementioned availability of ab road selection of clickable functional building blocks.…”
Section: Azide-and Alkyne-decorated Bifunctional Chelatormentioning
confidence: 99%